The decline of Fraxinus angustifolia Vahl in a Mediterranean salt meadow: Chlorophyll fluorescence measurements in long-term field experiment. (5th December 2020) - Mevy, J.P.; Guibal, F.; Lecareux, C.; Miglietta, F.
Abstract: The ecological transition zones also known as ecotones are specific ecosystems but how global change will affect their biodiversity and functioning is poorly understood. In the case of the areas at the interface between riparian forest and salt meadows the biodiversity conservation remains a major issue. The aim of this work was to evaluate the effects of a salty environment on Fraxinus angustifolia a non-halophyte species. For this, the photochemistry of PSII was in situ explored during the summer between 2007 and 2016. The predawn maximum quantum efficiency of PSII (Fv/Fm) was always greater than 0.8 which indicates an absence of chronic photoinhibition induced by salinity. During these years, the light kinetic of the actual quantum yield of PSII (ΦPSII ) was studied. It appears that this yield is generally higher in salty environments than in the riparian forest. Multivariate analysis, showed that the dissipation regulated light energy faction (ΦNPQ ), the photochemical quenching (qP) and the Fd/Fs ratio constitute the main explanatory variables of ΦPSII changes. The subsequent two-way-ANCOVA carried out demonstrated that ΦNPQ was weaker in saline environments, suggesting a better efficiency of photosystem collecting antennas. Meanwhile, the analysis of photosynthetic pigments did not exhibited a salt effect except the significant accumulation of chlorophyll a in 2016. In order to address the question of the salt-related toxicity, sodium ion contents in the leaves were found to be identical in the two sites, suggesting the establishment of an energy-dependent mechanism of salt exclusion/retention in roots. The growth rings of F. angustifolia in saline areas highly follows the annual water deficit changes. Between 2007 and 2016, the biomass in the salt meadow was higher with a peak in 2011 representing 60% of the biomass of control individuals. But, since 2011 a continuous decline of growth was recorded. Water conditions seem to constitute a limiting factor even if the photosynthetic apparatus generates the excess metabolic energy necessary to cope with the saline toxicity. This study thus highlighted the plasticity of the photochemistry of the PSII depending to the environmental conditions of the salt meadows. It also shows the vulnerability of an ecotone through the decline in the productivity of a glycophyte with climate change. This augurs for changes in the composition of plant communities which is in favor of strict halophytes. Highlights: Adaptation of a glycophyte as Fraxinus angustifolia to salt meadow is determined by: An increase of the quantum yield of PSII and chlorophyll a contents. A lower quantum yield of the Non-Photochemical energy loss in PSII (ΦNPQ). A higher photochemical quenching (qP) and the ratio Fd/Fs. A decrease of the tree-rings growth since 2011, suggesting changes in salt meadow plant communities with global change.